Association between vitamin levels and geriatric hip fractures: A cross-sectional study - He, Qifei; Zhang, Chun; Xie, Wei; Deng, Zhaoqiang; Yang, Shiwei; Li, Xia; Sun, Wei (Frontiers in Nutrition, 2025)
ObjectivesGeriatric hip fractures, known as osteoporotic fractures, are associated with nutritional deficiencies such as vitamin D (VitD). However, the relationship between other vitamins besides VitD and fracture is still lacking. Therefore, we intended to identify various vitamin levels and deficiencies in elderly patients with hip fractures and compared those with healthy elderly individuals.MethodsA total of 210 geriatric hip fracture continuous patients and 402 healthy elderly individuals aged ≥65 years old and with complete serum vitamin records were enrolled in this study. The levels of serum VitA, VitB1, VitB2, VitB3, VitB5, VitB6, VitB9, VitE, VitK1, and 25-hydroxyvitamin D (25-HO-VitD) and nutritional markers, such as prognostic nutritional index (PNI), were compared between geriatric hip fracture patients and healthy control. The correlation between vitamin level and the nutritional markers was explored. A multiple linear regression analysis was conducted to assess the association between vitamin levels and hip fracture.ResultsThe levels of VitA, VitB1, VitB3, VitB5, VitB9, 25-HO-VitD, 25-HO-VitD3, E, and K1 were all lower in the hip fracture group (p < 0.05). More than 80% of older persons suffered 25-HO-VitD deficiency in both healthy and fracture groups. A positive correlation between levels of VitA and nutritional markers existed in the fracture and healthy groups. In regression analysis, the association strength between standardized vitamin levels and fracture was the most significant in VitB9 (β = −0.94; 95%CI, −1.15 to −0.73; p < 0.001), VitA (β = −0.83; 95%CI, −1.04 to −0.61; p < 0.001), and VitK1 (β = −0.80; 95%CI, −1.02 to −0.58; p < 0.001), with no significant statistic difference found in VitB2, VitB9, 25-HO-VitD2, and 25-HO-VitD3.ConclusionVitamin D deficiency is common in elderly people with or without fracture. The levels of VitA, VitB9, and VitK1, instead of VitD, were much lower in fracture patients than in the healthy control, even controlling age and gender. VitA is a potential target for hip fracture prevention.